Nilai-Nilai Islam Dalam Tradisi Tingkeban di Kelurahan Ngampel Kota Kediri - Putri, Ayu Septiana; Khayu, Abdul; Aprilia, Try Heni (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: Tingkeban is a traditional Javanese ceremony associated with the age of the baby seven months in them womb. The Tingkeban ceremony at seven months of pregnancy is the last ceremony before childbirth, in which prayers are offered for the safety and normal delivery of mother and child. "Mitoni" is another name for the Tingkeban tradition which comes from the word "pitu" meaning "seven", another name for the Tingkeban tradition. This traditional ceremony aims to celebrate seven months of pregnancy. Tingkeban in Javanese culture is an ancient custom that is passed down from one generation to the next. Tingkeban, a tradition popular among Javanese people, has strong and deep Islamic values. In the tradition, Islamic values are clearly visible in various aspects. Firstly, there is a joint prayer led by an ustadz or kiaiKiyai. This prayer invokes God's protection for the mother and child, as well as a smooth delivery process. Secondly, the tradition reflects the Islamic principle of gratitude, where families express their gratitude to God for the blessing of pregnancy. This research aims to find out the tradition of tingkeban in Ngampel Village, Mojoroto Kec, Kediri City. The method used is a qualitative method through field observations and interviews with several local communities, with residents of Ngampel Village, Kediri City as the research subject. Through the results of the research, it can be seen that the tradition of tingkeban until now by the local community is still used to create harmony between customary practices and religious beliefs.Keywords: Tingkeban Tradition, Javanese Culture and Society